COMPOSITION TYPE AND ABUNDANCE OF PHYTOPLANKTON IN TELUK BAYUR WATERS PADANG WEST SUMATRA - Andi Darlianto; Aras Mulyadi; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                This research was conducted in March 2018 - April 2018 in Teluk Bayur, Padang Selatan Subdistrict, West Sumatra Province. The purpose of this research is to determine the type composition and abundance of phytoplankton in the waters of Teluk Bayur Padang, West Sumatra. Survey method was used in this research. Water quality measured in this research is temperature, pH, DO, Salinity, Nitrate, Phosphate, and Current speed. Phytoplankton composition in Teluk Bayur waters is composed by 5 class which is  Bacillariophyceae, Dinophyceae, Cynophyceae, Coscinodiscophyeae and Mediophyceae with total 16 species. The highest phytoplankton abundance in Teluk Bayur waters is found in stasiun 1 total 83,3 (ind/l) and the lowest abundance is in station 4 total 69,9 (ind/l). The highest relative abundance of phytoplankton species at station 1 is Leptocylindrus sp as much as 25%, at station 2 the highest is Streptotheca sp as much as 26%, at station 3 is Leptocylindrus sp and Surella sp as much as 16.3% and at station 4 namely Isthimia sp as much as 22.5%. Key word : Water quality, Phytoplankton, Teluk Bayur